Estrabismo divergente en paciente femenino de 7 años de edad. - Aguilera Sipion, Jordy Ronaldo (2023)
The deviation or loss of ocular parallelism is known as strabismus, which affects focusing and binocular vision. This is an eye condition that occurs more commonly in children than in older children. There are several causes of strabismus, among them we can mention optic nerve injuries or malfunction of the muscles that control the eyes, it is of utmost importance to detect it in time and provide adequate treatment. In this case study we analyze the situation of a 7-year-old patient with divergent strabismus, which is where the ocular parallelism is lost in the right eye and this is directed outward, hence the name divergent. The main objective of the optometrist is to provide an adequate corrective treatment to improve the patient's visual status. Once the analyses and examinations necessary for the diagnosis are completed, it is determined to apply the treatment of ocular occlusion and the use of bifocal lenses.